Impacts of Weak Sea Surface Temperature Warm Anomalies on Local Trade Cumulus Cloudiness in Large Eddy Simulations - Xuanyu Chen; Juliana Dias; Brandon Wolding; Peter N. Blossey; Charlotte DeMott; Robert Pincus; Elizabeth J. Thompson (Journal of Advances in Modeling Earth Systems, 2025)
Abstract This study investigates the local impact of weak sea surface temperature (SST) warm anomalies on trade cumulus cloudiness in an idealized and ensemble framework with large‐eddy simulations. The control experiment uses a spatially uniform, time‐invariant SST and mean large‐scale conditions and atmospheric forcings derived from the Atlantic Tradewind Ocean‐Atmosphere Mesoscale Interaction Campaign. The perturbed experiment adds a Gaussian warm SST anomaly (SSTA) with a 12.5 km radius and 0.5 K magnitude. The ensemble‐averaged differences between perturbation and control experiments show that cloud fraction is enhanced over the downwind half of the prescribed warm SSTA, with the enhancement peaking slightly above the environmental lifting condensation level (LCL) and then decaying with height. Compared to the upper‐level (>1.5 km) cloud response, the low‐level cloud response (<1 km) to the warm SSTA is stronger and occurs more systematically across different ensemble members. This near‐LCL cloud response is driven by enhanced surface buoyancy flux and buoyancy‐driven turbulence over the warm SSTA as opposed to SSTA‐induced anomalous surface convergence and mesoscale ascent. Process denial experiments indicate that the locally enhanced surface sensible and latent heat fluxes contribute almost equally to increase the near‐LCL cloudiness, even though the locally enhanced surface sensible heat flux plays a dominant role in enhancing surface buoyancy flux. These results corroborate recent satellite composite results (Chen et al., 2023, https://doi.org/10.1175/jas‐d‐23‐0075.1), suggesting that the observed increase of daily cloud fraction above warm SSTAs is due to more frequent turbulence‐driven formation of shallow cumuli near the cloud base.